2019
DOI: 10.21608/jrciet.2019.33606
|View full text |Cite
|
Sign up to set email alerts
|

Developing Reading Comprehension Skills Using Sheltered Instruction Observation Protocol ( SIOP) among EFL Students

Abstract: reading comprehension skills were identified through developing a checklist. In light of the skills identified, a pre-post reading comprehension test was constructed and validated by a panel of EFL jurors .The participants, totaling 68, were divided into two equal groups of 34 students in the experimental group and 34 students in the control. The experimental group students received English reading comprehension instruction using SIOP model, while the control group students received regular reading comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…This could be attributed to the use of visuals, such as posters, which helped improve the participants" interaction as well as vocabulary learning. These findings are consistent with those obtained by Al Saraein (2017); Ebedy (2018); Rivera (2019);and Chandler (2020).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This could be attributed to the use of visuals, such as posters, which helped improve the participants" interaction as well as vocabulary learning. These findings are consistent with those obtained by Al Saraein (2017); Ebedy (2018); Rivera (2019);and Chandler (2020).…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the participants" reading abilities improved after being taught by using the SIOP model. This result copes with those obtained by El Ghotmy (2018) Ebedy (2018);and Rivera (2019). If an English learner can read in the first language, then these cognitive abilities can be transferred to reading in English.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The multi-faceted and complicated roles of teachers on multiple levels (i.e., student level, classroom level, school level and community level) have led to the development of instructional practices and models that help teachers integrate new knowledge, adapt their learners' needs, and utilize different resources (Caena, 2013, pp 30-31). Recent research asserted the need to utilize the sheltered instruction observation protocol (SIOP), as a key model that addresses the challenges faced by teachers, for enhancing the professional development of EFL pre-service or in-service teachers (Ebedy, 2019 andShort, Fidelman, &Louguit, 2012). The model was initially utilized as an observation instrument to measure teachers' implementation of sheltered instruction techniques and then evolved into a framework for lesson planning and delivery .…”
Section: Review Of Literaturementioning
confidence: 99%
“…It was concluded that the SIOP model improved the quality of instruction to the learners and increased their level in English language. In her attempt to develop reading comprehension skills, Ebedy (2019) utilized the SIOP model among sophomore English majors at the Faculty of Foreign Languages and Translation. Sixty-eight students, divided into two equal groups, participated in the study.…”
Section: Review Of Literaturementioning
confidence: 99%